The “Connectivome Theory”: A New Model to Understand Autism Spectrum Disorders - Zoccante, Leonardo; Ciceri, Marco Luigi; Gozzi, Luigi Alberto; Gennaro, Gianfranco Di; Zerman, Nicoletta (Frontiers in Psychiatry, 2022)
The classical approach to autism spectrum disorders (ASD) is limited to considering their neuro-functional aspects. However, recent scientific literature has shown that ASDs also affect many body systems and apparatuses such as the immune system, the sensory-motor system and the gut-brain axis. Medical literature suggests that connective tissue can be considered the common thread linking all these structures. Connective tissue, depending on its different anatomical sites, can perform functions of connection, support (serous sheaths) and as a "connective barrier"; that is, it is a structure responsible for separation from the external environment and protection of the internal environment (skin), the regulated interchange between the two (intestine, pulmonary alveoli, sense organs) and immunological surveillance (interstices). There is a close relationship between connective tissue, the central nervous system, the musculoskeletal system and the immune system. Alterations in connectivity are common to various developmental disorders, including ASD; therefore, alterations in the physiological activity of microglia could be implicated in the pathogenesis of these disorders. Muscle hypotonia tends clinically to correlate with an altered sensoriality and, in fact, it is not uncommon for discomfort or early muscle fatigue to be reported in ASDs. People with ASD, whose intestinal connectivity is reduced, often have dysfunctions of the hive, phenomena of malabsorption and leaky gut syndrome. In addition, at the cutaneous and subcutaneous levels there is a greater predisposition to inflammatory events due to the lack of adequate release of anti-inflammatory mediators. Alveolar-capillary dysfunctions have also been found in ASD. Among the most frequent clinical manifestations are immune-mediated forms of allergic asthma and bronchial hyper-reactivity or inflammatory pathologies of the pulmonary interstitium. Therefore, in autism, altered connectivity can result in phenomena of altered sensitivity to environmental stimuli (sense organs, primarily sight and hearing). The following interpretative model, whose underlying rationale we define as "connectivome theory", entails the evaluation and interpretation of ASDs through highlighting somatic elements, which are not adequately considered in the more classic intervention models. We believe that this broader approach could be helpful for a more accurate analysis, as it is able to enrich clinical evaluation and define more multidisciplinary and personalized interventions.